Déprédation des glands de chêne liège par les insectes et possibilités de germination et de croissance des semis - BOUCHAOUR-DJABEUR, Sabéha; BENABDELI, Khéloufi; Bejamaa, Mohamed Lahbib; Stiti, Boutheina (Geo-Eco-Trop, 2011)
Depredation of the acorns cork oak by the insects and its impact on the potential of germination and seedling growth were studied in a mountain cork oak forest in northwestern Algerian. The rate of pre-germinated acorns on the ground is higher than for other acorns. The weight is the most distinctive variable for all the acorns; whatever their condition and provenance, it varies significantly from 0.76 to 6.76 g. Regarding the damage to acorns, statistical tests show no significant difference in the length and weight, it is not very significant for the width.The infestation of acorns is independent of their size. The acorns attacked by beetles are clearly dominant (72%) compared with those attacked by moths (28%). 20% severely damaged acorns germinate and produce viable seedlings. But the germination rate decreases with the increase of injuries. Growth is strongly affected by the rate of damage to acorns. One therefore concludes that a major attack in the cotyledons certainly does not act on germination, but can affect the strength of the resulting plant and its survival.
Keywords: aspects of the acorns; Growth; infest by the insects; period of harvest; Quercus suber L.; resistance

Phytophthora kernoviae and P. ramorum: host susceptibility and sporulation potential on foliage of susceptible trees1 - Denman, S.; Kirk, S.; Whybrow, A.; Orton, E.; Webber, J. F. (EPPO Bulletin, 2006)
Phytophthora kernoviae and P. ramorum are introduced, invasive pathogens in the UK. Both species are adapted for aerial dispersion and have a wide host range, many of which are common to both pathogens. The diseases they cause are foliar necrosis and shoot tip dieback on both tree and ornamental hosts, and bleeding cankers on tree hosts. Inoculum is produced on infected foliage but not on bleeding cankers in both cases. Proactive measures to prevent disease spread and to evaluate the risks posed by these pathogens are being undertaken. Amongst others, these include using the detached leaf assay to get an indication of tree foliage susceptibility, and inoculating wounded stems of saplings to get an idea of under-canopy sapling and nursery tree susceptibility. The sporulation potential on selected susceptible hosts was assessed, and finally, surveys which are still ongoing were carried out in south-west England. Results of this work are presented and discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: host tree; Phytophthora kernoviae; Phytophthora ramorum; resistance; sporulation potential (voyant); susceptibility

Phytophthora kernoviae and P. ramorum: host susceptibility and sporulation potential on foliage of susceptible trees1 - Denman, S; Kirk, S; Whybrow, A; Orton, E; Webber, J F (EPPO Bulletin, 2006)
Phytophthora kernoviae and P. ramorum are introduced, invasive pathogens in the UK. Both species are adapted for aerial dispersion and have a wide host range, many of which are common to both pathogens. The diseases they cause are foliar necrosis and shoot tip dieback on both tree and ornamental hosts, and bleeding cankers on tree hosts. Inoculum is produced on infected foliage but not on bleeding cankers in both cases. Proactive measures to prevent disease spread and to evaluate the risks posed by these pathogens are being undertaken. Amongst others, these include using the detached leaf assay to get an indication of tree foliage susceptibility, and inoculating wounded stems of saplings to get an idea of under-canopy sapling and nursery tree susceptibility. The sporulation potential on selected susceptible hosts was assessed, and finally, surveys which are still ongoing were carried out in south-west England. Results of this work are presented and discussed.
Keywords: host tree; Phytophthora kernoviae; Phytophthora ramorum; resistance; sporulation potential (voyant); susceptibility

The resistance of cork to decay by wood-destroying molds - DeBaun, Robert M; Nord, F F (Archives of Biochemistry and Biophysics, 1951)
A new method for the determination of the lignin in cork has been reported. This procedure gives values ca. 25–30%. It is based on the colorimetric estimation of the lignin released by autoclaving with alkali. Using this method it was shown that cork is highly resistant to decay by brown-rot wood-destroying molds. This is attributed to the protective action of the suberin or to the presence in the cork of substances toxic to the molds.
APS
Keywords: Cork; Lignin; molds; resistance